2016
DOI: 10.1016/j.pharep.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of testosterone on cardiovascular risk factors in men with type 2 diabetes and late-onset hypogonadism treated with metformin or glimepiride

Abstract: Our results suggest that testosterone may bring more clinical benefits to metformin- than sulfonylurea-treated men with diabetes and LOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The increase of serum Hcy concentration in the metformin-treated patients was confirmed by a series of observational studies [16][17][18]20,25,[52][53][54][55][56]. These studies indicated that metformin was associated with an elevated concentration of serum Hcy compared with control treatment.…”
Section: Discussionmentioning
confidence: 79%
“…The increase of serum Hcy concentration in the metformin-treated patients was confirmed by a series of observational studies [16][17][18]20,25,[52][53][54][55][56]. These studies indicated that metformin was associated with an elevated concentration of serum Hcy compared with control treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Glimepiride had significant effect and safety on lowering blood glucose. At the same time, the latest research showed that there was no obvious change in T levels before and after alone treatment of GLI in men with T2D and late‐onset hypogonadism (LOH) (Krysiak et al., ). Therefore, oral sulphonylureas alone might not improve the sexual function of patients with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Glimepiride (GLI), as one of commonly used sulfonylureas, has significant effect and safety on lowering blood glucose. However, a new study shows that oral GLI may have no obvious effect on T levels (Krysiak, Gilowski, & Okopień, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although ED is present in many non-diabetic men, ED may be considered as an early diabetic complication [13]. In Africa, the prevalence of diabetes-associated ED has largely varied, a prevalence of 67.9% has been reported in patients with DM in Ghana [14], 57.4% in Nigeria [15], and 75% in Benin [16].…”
Section: Introductionmentioning
confidence: 99%